Analysis of pesticide residues in the vegetables by using gas chromatography - electron capture detector - Phillisca Prima , Adan (2013)
Over the last few decades, the Malaysian agriculture industry has contributed to the growth and major contributors to national income and export earnings. It is become basis of economic growth and main contributor in national economy prior to the 1970s. However, in order to increase the food production such as vegetables and fruits, pesticides is widely used in agriculture industry to prevent, destroying or mitigating any pest that can cause harm to plant. Unfortunately, the pesticide residue level in vegetables is dangerous and can cause harm to human health if excessive consumption of pesticides in vegetables is highly taken. Commonly, people tend to wash the vegetables only by using tap water before cook or eaten raw without knowing kevel of food safety before these commodities been consumed. Thus, the objective of this thesis are to determine and compare the concentration of pesticide residue level in selected vegetables after being washed by using distilled water and vegetables detergent and to determine the food safety of these commodities by comparing the pesticides concentration result with Malaysian Maximum Residue Limits standard that has been listed out by Ministry of Health under Food Regulation 1985. In this study, presence of chlorpyrfos pesticides is detected in cabbage and eggplant vegetables. Both vegetable samples are washed and soaked with distilled water and vegetables detergent (Pureen Liquid Cleanser) before sample preparation is made and analyzed by using Gas Chromatogrpahy-Electron Capture Detector method. From the result, it has showed the presence of chlorpyrfos pesticide in both vegetable samples and concentration pesticides residue is lower when washed and soaked with vegetables detergent compare when washed and soaked with distilled water. It proved that vegetable detergent is an effective way to remove or kill the pesticide residue that left in these vegetable. Result from this study then is compare with Maximum Residue Limits to determine the level of food safety of this type of commodities and from the comparison, concentration of pesticides residue in vegetable could not be consider a serious public health problem. However, continuous monitoring and tighter regulation of pesticide residue of chlorpyrjfos in vegetables is recommended.